2021
DOI: 10.1002/jsp2.1171
|View full text |Cite
|
Sign up to set email alerts
|

Paraspinal muscle pathophysiology associated with low back pain and spine degenerative disorders

Abstract: Low back pain disorders affect more than 80% of adults in their lifetime and are the leading cause of global disability. The muscles attaching to the spine (ie, paraspinal muscles) are critical for proper spine health and play a crucial role in the functioning of the spine and whole body; however, reports of muscle dysfunction and insufficiency in chronic LBP (CLBP) patients are common. This article presents a review of the current understanding of the relationship between paraspinal muscle pathophysiology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 133 publications
(280 reference statements)
3
35
0
Order By: Relevance
“…In the current study, the CSA and TCSA values of males were found to be higher than those of females. Previous studies have also shown greater CSA and higher density of paraspinal muscles in males than in females [17,19,27,61,71,72]. The current study results were consistent with literature.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the current study, the CSA and TCSA values of males were found to be higher than those of females. Previous studies have also shown greater CSA and higher density of paraspinal muscles in males than in females [17,19,27,61,71,72]. The current study results were consistent with literature.…”
Section: Discussionsupporting
confidence: 92%
“…The paraspinal muscles are of critical importance for spinal health. Parspinal muscle dysfunction and failure is common in patients with low back pain [19]. LDH and other causes of low back pain, and many spine pathologies cause changes in the paraspinal muscles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These muscles play a key role in maintaining lumbar segment stability and dynamic regulation; they can maintain the posture and restrict excessive intervertebral movement [ 8 , 9 ]. Previous studies have observed structural remodeling of paraspinal muscles in LDD, including fatty infiltration, asymmetry, and decreased size [ 2 , 10 , 11 ]. Among them, fatty infiltration of paraspinal muscles is closely related to high-intensity pain/disability and structural abnormalities in the lumbar spine [ 6 , 12 15 ].…”
Section: Introductionmentioning
confidence: 99%